Knee–Hip–Spine Syndrome: Improvement in Preoperative Abnormal Posture following Total Knee Arthroplasty - Yasushi Oshima; Nobuyoshi Watanabe; Norishige Iizawa; Tokifumi Majima; Mitsuhiro Kawata; Shinro Takai (Advances in Orthopedics)
An ergonomic upright body posture is maintained by the alignment of the spine, pelvis, and lower extremities, and the muscle strength of body trunk and lower extremities. The posture varies with age because of the degenerative changes in the involved structures and the weakening of the muscles. The compensatory mechanisms underlying these changes have recently been evaluated, and the loss of lumbar lordosis results in spinal kyphosis, pelvic retroversion, hip extension, knee flexion, and ankle dorsiflexion. These mechanisms are referred to as the hip–spine and knee–spine syndromes. The spine, hip, and knee are anatomically connected, and the pain and discomfort of the lower back, hip, and knee frequently arise due to degenerative changes of these structures. Thus, these mechanisms are considered as the knee–hip–spine syndrome. Spinal fusion, total hip arthroplasty, and total knee arthroplasty are the surgical procedures for severe degeneration, and their clinical outcomes for the affected sites are promising. However, despite surgeries, other structures may degenerate and result in complications, such as proximal junctional kyphosis and hip dislocation, following spinal fusion. Therefore, it is necessary to evaluate each patient under specific conditions and to treat each section while considering associations between the target structure and entire body. The purpose of this article is to introduce postural maintenance, variations with age, and improvements with surgical interventions of spine, hip, and knee as the knee–hip–spine syndrome.